Iconography and Iconology of The Aksi Kamisan Photo (13-2-2014) by Fanny Octavianus - Pamungkas Wahyu Setiyanto; Agus Triyana; Novan Jemmi Andrea (Journal of Urban Society's Arts, 2022)
The presence of photography as a medium of communication has transformed into an art that not only perpetuates reality in images (visuals), but also poetic values and/or image language. Likewise, journalistic photography works are created not only based on existing moments or events, but are also influenced by views, skills, and other factors inherent in the photographer. The photographer has the right to place his philosophical aspects based on the importance of his secondary needs. The creation of photographic works is the result of the integration of the social, spiritual and cultural life of the photographer, in this context as was done by Fanny Octavianus who consistently documented the Aksi Kamisan by activists to demand that the government resolve cases of human rights violations. The consistency of the Aksi Kamisan becomes a strength that makes this action full of values that can be observed through the signs implied in every action they take. From this explanation, Fanny’s work on Aksi Kamisan is studied through factual and expressive visual signs, themes and concepts, and also looks for the symbolic value in Fanny’s work. In carrying out this excavation and search, the method of art history uses the Iconography and Iconology approach of Erwin Panofsky. As a result, this study found that there were various visual markers of the Aksi Kamisan photo that were factual and expressive. Factual markers can be observed from formal aspects, while expressional markers are obtained from motion effects created by controlling the camera using slow motion techniques. The symbolic values conveyed in this Aksi Kamisan photo are the era of openness in conveying people’s opinions directly to the government, which can be seen as a symbol of cultural openness in the reform era. Ikonografi dan Ikonologi Foto Aksi Kamisan (13-2-2014) Karya Fanny Octavianus. Kehadiran fotografi tidak saja mengabadikan realitas dalam gambar (visual), namun juga nilai puitis dan atau bahasa gambar. Begitu juga dengan karya fotografi jurnalistik yang tercipta tidak sekadar berdasarkan momen atau peristiwa, tetapi dipengaruhi oleh pandangan, kemampuan keterampilan, dan faktor lain yang melekat pada diri fotografernya. Fotografer berhak menempatkan aspek filosofisnya berdasarkan kepentingan kebutuhan sekundernya. Penciptaan karya foto merupakan hasil dari integrasi kehidupan sosial, spiritual dan kebudayaan si pemotret, dalam konteks ini seperti yang dilakukan oleh Fanny Octavianus yang konsisten mendokumentasikan Aksi Kamisan yang dilakukan para aktivis untuk menuntut pemerintah menuntaskan kasus pelanggaran Hak Asasi Manusia (HAM). Konsistensi aksi Kamisan menjadi sebuah kekuatan yang menjadikan aksi ini penuh dengan nilai yang dapat diamati melalui tanda-tanda tersirat dalam setiap aksi yang dilakukan. Dari pemaparan tersebut, karya Fanny tentang Aksi Kamisan dikaji melalui tanda-tanda visual yang bersifat faktual dan ekspresional, tema dan konsep, dan juga dicari nilai simbolik yang ada dalam karya Fanny tersebut. Dalam melakukan penggalian dan pencarianini menggunakan metode sejarah seni dengan pendekatan Ikonografi dan Ikonologi Erwin Panofsky. Hasilnya, penelitian ini menemukan adanya berbagai penanda visual foto Aksi Kamisan yang bersifat faktual dan ekpresional. Penanda faktual dapat diamati dari aspek-aspek formal, sedangkan penanda ekspresional didapat dari efek gerak yang diciptakan dengan pengendalian kamera menggunakan teknik slow motion. Nilai-nilai simbolik yang disampaikan dalam foto Aksi Kamisan ini adalah era keterbukaan dalam menyampaikan pendapat rakyat langsung kepada pemerintah bisa dipandang sebagai simbol keterbukaan kultur era reformasi.